Adesão do Hospital Universitário da Universidade Federal de Santa Maria à Ebserh: um estudo dos efeitos da regulação assistencial sobre o absenteísmo ambulatorial - Cioccari, Daniela Gomes (2023)
This study identifIed the effects of the Care Regulation Guidelines (DRA), for outpatient management processes, on outpatient absence rates at the Santa Maria University Hospital (HUSM). We described and compared the implementation of the DRA before and after outpatient management process through qualitative research and analyzes using the content analysis method. Interviews were carried out with the professionals responsible for implementation to analyze the managers’ perception of the implementation. In the quantitative part, data were collected from HUSM statistical reports to analyze the rates of outpatient absence in two periods, before and after the implementation of the DRA using the descriptive statistics technique, horizontal and vertical analysis. Although, the interviewed professionals considered that several improvements were implemented with the DRA, such as improving the quality of information, regulating access and meeting quantitative and qualitative goals contracted with the SUS, the research results demonstrated a general increase in rates of outpatient absence in the specialties selected in the analysis, with a consecutive reduction during the years analyzed, in the rate of outpatient absence only in the specialty Rheumatology, and Ophthalmology stood out as the specialty with the greatest increase and growing rate of outpatient absence Based on these data, it was possible to develop a proposal that contributes to the duties of the unit responsible for outpatient management, to mitigate outpatient absence and rationalize available resources, aiming for more modern and effective management.